Condições de vida e saúde dos idosos no município de Coxilha-RS - Mascarelo, Andréia (2011)
The elevation of the number of elderly people has become a new and immediate social, political, economic and health problem. Due to this greater survival rate, the chronic diseases - which influence in a negative way the autonomy and independence of the elderly people - have been occurring frequently and increase the pursuit of health care services and the cost for the elderly people, for their families, for the public healthcare system and for society too. So, it is extremely relevant the development of public policies which focus on the elderly people their autonomy and independency as long as possible. Therefore, the aim of this study a transversal one - is to know the life and health conditions of all the elderly people - aged 60 years or more - who live in a countryside city Coxilha - in Rio Grande do Sul (RS). The data collection was done through the adaptation of the instrument of Health, Well-being and Aging project (SABE), the Geriatric Depression Scale (GDS) and the Mini-Mental State (MMS). It was done through a home inquiry, carried out by psychologists between June and July, 2010. The research was approved by the Ethics and Research Committee of the University of Passo Fundo, Statement No. 148/2010. The data was analyzed by descriptive statistics. The level of significance that was used was 5%. Coxilha city has 12.4% of elderly people, mean age 69.4 (±7.7) years, most of them 52.3% - are female and 68.6% were declared as white people; 57.7% of the elderly people live in the urban area, 82.8% live with someone else, 52.6% live in houses which have belonged to their families only; 63.2% are married; 87.0% are catholic; 81.0% are retired, 38.2% have a total monthly income of one or two minimum wages and 82.1% attended school. The mean scores in the MMS was 21.9 (±5,8) with a better performance of the younger men with a higher level of education. Most of them live in their own houses 92.7%; 100.0% have water supply; 90.0% have bathrooms and 99.4% have electric energy supply. The self-evaluation of health was negative and predominant 54.0%; 57.0% consider their health to be better than the other people who are in the same age, and 39.4% say it is the same as one year ago. Elderly people with chronic pain 50.3%, and that in the most of the cases are related to their backs 67.4%. Fall happened with 25.4% of the elderly people, and with fracture 26.5%. Hearing loss was mentioned by 46.5% and eyesight loss by 89.1%. In the last two years 59.6% of the women did not have mammograms and 53.2% did not have screening test for cervical cancer. Most of the men 63.3% - had a prostate exam. Among the population studied, 71.3% do not consume alcoholic beverages and 19.0% do not smoke. The use of medication was mentioned by 77.3% - 38.1% of the medications are provided by SUS or Health Care centers. Physical activities are practiced by 45.0%, and walking by 91.4%. The most prevalent health problem was the nervous problems 63.0% and the one that really brings troubles to their daily lives is the spine problems 42.6%. The GDS scores average were 3.1 (±2,4), with a prevalence of depression results for younger and widower men, and with more than seven years of school attendance. Most of them are able to accomplish the basic activities of a daily life in an independent way. Whenever they are sick, 59.7% go to the Health Care center, 93.9% are seen by a doctor and 48.9% in the same day they required a consultation. Most of them 96.4% - have a caregiver who helps them whenever they need, 36.1% are elderly people too, mostly women 76.2% and spouses 44.2%. The main care received is companionship 98.7%. The ones who received institutional care/assistance were 24.9%. This sort of study provides conditions for the implementation of actions which are concerned with elderly people and contribute to the optimization of the limited resources which are available to the Healthcare department. Moreover, it enables people to know the life conditions of elderly people, promoting the development of public policies which are consistent with the real necessities of the population that is aging, within its different scenarios